2014
DOI: 10.3109/09537104.2014.932339
|View full text |Cite
|
Sign up to set email alerts
|

CD40L expression in plasma of volunteers following LPS administration: A comparison between assay of CD40L on platelet microvesicles and soluble CD40L

Abstract: CD40 ligand (CD40L) is a transmembrane protein that is mainly expressed on activated T cells and platelets. This protein, however, may also be shed from cells and circulate in the blood in a soluble form. "Soluble CD40L" has attracted interest as a biomarker as it can interact with CD40 and elicit cellular responses involved in the pathophysiology of various thrombotic and inflammatory conditions. As platelets can release microvesicles following activation, we investigated the expression of CD40L on circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…By other approaches, levels of these markers have all been shown to be elevated in the blood of SLE patients171819. Of note, previous studies have shown that both sCD40L and HMGB1 can be MP components2021. The data presented in Fig.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…By other approaches, levels of these markers have all been shown to be elevated in the blood of SLE patients171819. Of note, previous studies have shown that both sCD40L and HMGB1 can be MP components2021. The data presented in Fig.…”
Section: Resultsmentioning
confidence: 79%
“…As PMPs carry CD40L from the site of platelet activation, they could promote activation of cells in the periphery as well as the immediate surroundings. We have recently demonstrated that assay of CD40L positive MPs may represent a more sensitive approach for sCD40L determinations compared to ELISA assays, suggesting that assay of “soluble’ markers on particles may represent a useful analytic approach21. Relevance of such assessment comes from studies indicating that levels of CD40L on immune cells as well as sCD40L are increased in SLE and links to disease activity and activation of B-cells and the type I IFN system have been reported333435.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the two assays could be related to sensitivity. We have previously shown that measurement of soluble proteins on MPs yields higher sensitivity, as the flow cytometer only measures proteins bound to particles, whereas ELISA measures both bound and soluble proteins [36]. A previous study by Vlachoyiannopoulos et al showed that b 2 GPI levels in patients with APS were higher than those in SLE patients negative for aCLs [37].…”
Section: Discussionmentioning
confidence: 98%
“…Our results, together with the findings by Yamamoto et al ., raise for the possibility that sCD40 ligand may be used as a biomarker of disease activity. In this regard, we have recently provided data suggesting measurements of CD40 ligand on platelet‐MVs may be a more sensitive marker of inflammation than sCD40 ligand . P‐selectin is mainly expressed on activated platelets and plays a role in the recruitment of leucocytes by binding to its ligand, P‐selectin glycoprotein ligand‐1 .…”
Section: Discussionmentioning
confidence: 99%